Rheumatoid arthritis and mitochondrial homeostasis: The crossroads of metabolism and immunity - Liu Cui; Jing Weiyao; Su Chenghong; Liu Limei; Zhang Xinghua; Yuan Bo; Du Xiaozheng; Wang Haidong (Frontiers in Medicine, 2022)
Rheumatoid arthritis is an autoimmune disease characterized by chronic symmetric synovial inflammation and erosive bone destruction. Mitochondria are the main site of cellular energy supply and play a key role in the process of energy metabolism. They possess certain self-regulatory and repair capabilities. Mitochondria maintain relative stability in number, morphology, and spatial structure through biological processes, such as biogenesis, fission, fusion, and autophagy, which are collectively called mitochondrial homeostasis. An imbalance in the mitochondrial homeostatic environment will affect immune cell energy metabolism, synovial cell proliferation, apoptosis, and inflammatory signaling. These biological processes are involved in the onset and development of rheumatoid arthritis. In this review, we found that in rheumatoid arthritis, abnormal mitochondrial homeostasis can mediate various immune cell metabolic disorders, and the reprogramming of immune cell metabolism is closely related to their inflammatory activation. In turn, mitochondrial damage and homeostatic imbalance can lead to mtDNA leakage and increased mtROS production. mtDNA and mtROS are active substances mediating multiple inflammatory pathways. Several rheumatoid arthritis therapeutic agents regulate mitochondrial homeostasis and repair mitochondrial damage. Therefore, modulation of mitochondrial homeostasis would be one of the most attractive targets for the treatment of rheumatoid arthritis.